2020
DOI: 10.1177/2055102920933073
|View full text |Cite
|
Sign up to set email alerts
|

Success of assisted reproductive technology treatment and couple relationship: A pilot study on the role of romantic attachment

Abstract: Infertility is a deeply distressing experience, which can threaten important personal and martial goals, frequently affecting the psychophysical health. A supportive relationship and a secure romantic attachment appear to reduce infertility stress, as well as play a relevant role in the success of assisted reproductive technology treatments. The principal aim of the study is to investigate the predictive effect of romantic attachment, couple characteristics, quality of life and age on assisted reproductive tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Noteworthy, specifically referring to the significant influence of each partner's psychological symptoms on their experience of body avoidance and dissatisfaction, the current findings point to the relevance of providing specific and individual support to the couple's partners already from the very early stages of the ART procedure. This is also supported by past literature highlighting the need to provide psychosocial care to people initiating ART procedures, with the potential to prevent the development or the worsening of psychosocial difficulties and symptoms (Purewala et al, 2018) that could hinder the likelihood of ART cycles success (Purweal et al, 2017;Renzi et al, 2020aRenzi et al, , 2020bSimionescu et al, 2021).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Noteworthy, specifically referring to the significant influence of each partner's psychological symptoms on their experience of body avoidance and dissatisfaction, the current findings point to the relevance of providing specific and individual support to the couple's partners already from the very early stages of the ART procedure. This is also supported by past literature highlighting the need to provide psychosocial care to people initiating ART procedures, with the potential to prevent the development or the worsening of psychosocial difficulties and symptoms (Purewala et al, 2018) that could hinder the likelihood of ART cycles success (Purweal et al, 2017;Renzi et al, 2020aRenzi et al, , 2020bSimionescu et al, 2021).…”
Section: Discussionmentioning
confidence: 58%
“…Men are more likely to suppress painful and negative emotions, defending themselves from depression and depression-like symptoms ( Conrad et al, 2001 ). On the other hand, alexithymia measured on infertile women undergoing in-vitro treatments was associated with maladaptive coping strategies and psychological stress ( Gourounti et al, 2016 ) further considered as a risk factor for symptoms of anxiety, depression, psychological distress ( Juriü Vukeliü et al, 2019 ), and reduced quality of life ( Renzi et al, 2020a , 2020b ). Moreover, alexithymia also results as predictive of greater body checking and body dissatisfaction as compared to non-alexithymic women ( De Berardis et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult attachment was assessed using the Experiences in Close Relationships Inventory (ECR) 14 . ECR produces two scores: attachment-related avoidance and attachment-related anxiety scores.…”
Section: Experiences In Close Relationships Inventory (Ecr)mentioning
confidence: 99%
“…Some studies report that spouses struggling with infertility also recognize the positive aspects of this experience, namely an increased sense of intimacy and proximity [ 57 ]. While studies of infertile women treated with assisted reproductive technology have shown that the positive effects of treatment are associated with lower interpersonal intimacy and reluctance to reveal oneself in a romantic relationship [ 67 ].…”
Section: Introductionmentioning
confidence: 99%